A comprehensive study of piezomagnetic response in CrPS4 monolayer: mechanical, electronic properties and magnetic ordering under strains. (30th August 2017) - Joe, Minwoong; Lee, Hosik; Alyörük, M Menderes; Lee, Jinhwan; Kim, Sung Youb; Lee, Changgu; Lee, Jun Hee
Abstract: We performed first-principles calculations to investigate the magnetic, mechanical and electronic properties of the tetrachalcogenide CrPS4 . Although bulk CrPS4 has been shown to exhibit a low-dimensional antiferromagnetic (AFM) ground state where ferromagnetic (FM) Cr-chains are coupled antiferromagnetically, our calculations indicated that the monolayer can be transformed to an FM material by applying a uniaxial tensile strain of ⩾4% along the FM Cr-chain direction. The AFM-to-FM transition is explained to be driven by an increase of the exchange interaction induced by a decrease in the distance between the FM Cr-chains. A huge nonlinear piezomagnetism was predicted at the strain-induced magnetic phase boundary. Our study provides insight about rational design of single-layer magnetic materials for a wide range of spintronic devices and energy applications.